Three decades of financial sector risk - Joel F. Houston; Kevin J. Stiroh (Federal Reserve Bank of New York, 2006)
This paper examines the evolution of risk in the U.S. financial sector using firm-level equity market data from 1975 to 2005. Over this period, financial sector volatility has steadily increased, reaching extraordinary levels from 1998 to 2002. Much of this recent turbulence can be attributed to a series of major financial shocks, and we find evidence of an upward trend in volatility only for the common component that affects the entire financial sector. While idiosyncratic volatility remains dominant, a combination of common shocks, deregulation, and diversification has reduced its relative importance since the early 1990s. Within the financial sector, commercial banks show the largest rise in volatility, which also reflects industry shocks and not the idiosyncratic component. Despite these changes, we find that the links between the financial sector and economic activity have declined in recent years. These results have implications for investors, bank regulators, and other policymakers concerned with the origins of financial sector risk and with the links between the financial markets and real activity.
Keywords: G0; G2; 330; financial sector; volatility; risk Stiroh; Finanzsektor; Volatilität; Risiko; USA; Finanzmarktkrise